BIGCCS Innovations – Measures to Accelerate CCS Deployment. (January 2016) - Mølnvik, Mona J.; Aarlien, Rune; Henriksen, Partow P.; Munkejord, Svend Tollak; Tangen, Grethe; Jakobsen, Jana P.
Abstract: After six years in operation, BIGCCS International Research Centre is in its final phase, and results are being produced at high speed. The ultimate goal for the BIGCCS centre is to contribute to the acceleration of deployment of CCS technologies. Therefore, the Centre has put considerable emphasis on generating useful results to its industrial partners, and results with a significant potential for commercialization. The paper describes 22 of the most promising innovations identified under the Centre. These 22 innovations are related to capture, transport, storage and value chain, and are but a few of all potential innovations identified. The paper also discusses how BIGCCS has managed innovations, which are classified according to a nine-point Technology Readiness Level scheme.